Radar studies of ionospheric dusty plasma phenomena. Issue 6 (17th June 2019) - Mann, I.; Gunnarsdottir, T.; Häggström, I.; Eren, S.; Tjulin, A.; Myrvang, M.; Rietveld, M.; Dalin, P.; Jozwicki, D.; Trollvik, H.
Abstract : We discuss the influence of charged dust on radar observations in the Earth ionosphere. This region in the upper Earth atmosphere can be described as a partially ionized, low‐temperature plasma. Plasma parameters vary by orders of magnitude spatially and in time. Dust particles influence the charge balance, in some cases dusty plasma condition is met. The polar mesospheric echoes are an example of dust plasma interactions observed with radar. The mesosphere is a region where atmospheric temperature decreases with altitude and can reach frost point temperature. The formation of the polar mesospheric radar echoes involves neutral atmosphere dynamics, which is latitude dependent and it involves charged dust particles, especially icy dust that forms in the polar summer mesosphere. Charged dust can also influence incoherent scatter that results from electromagnetic waves scattering off electrons, where the electrons are coupled to other charged components. Observers rarely report charged dust signatures in the incoherent scatter spectra; we show that there is a good chance for doing so with improved observations. The incoherent scatter can possibly also be used to estimate the amount of charged dust in the direct vicinity of a meteor, as we show based on the order of magnitude considerations. This prospect of new observational results makes theoretical investigations of radio‐wave scattering in the presence of charged dust with size distributions worthwhile.